ChemInform Abstract: Synthesis under Moderate Pressure of 3‐Imidazo[1, 2‐a]pyridinylidene Pyrrol‐2‐ones. Issue 40 (September 2016) - Masurier, Nicolas; Lebrun, Aurelien; Canitrot, Damien; Chezal, Jean‐Michel; Moreau, Emmanuel
Abstract: Furan‐2‐ones (I) are converted into their pyrrol‐2‐one analogues upon treatment with aqueous ammonia under moderate pressure.